Strategi Pemasaran Produk Tabungan Haji Bank Mega Syariah di Kantor Kementerian Agama Kabupaten Lombok Timur - Maas Sabirin (ISLAMIKA, 2023)
The overall objective of this research is to explore marketing strategies and limit Mega Syariah hajj savings products in the area of the Ministry of Religion office in East Lombok Regency. The type of research in this research is field research using qualitative methods. In the process of collecting data, researchers used the method of observation, interviews and documentation. The results of the study concluded that the marketing of Bank Mega Syariah KCP East Lombok's haj savings products was carried out through 4 (four) strategies, namely: 1) product strategy, including guarantee offers, banking network transactions, competitive profit sharing, automatic zakat debit, directly connected with religious closure and free of charge management, 2) pricing strategy, setting standard prices starting from the lowest price of IDR 200,000 (with the installment method) to IDR 25,000,000 (direct share), 3) distribution strategy, carried out by inviting Muslims, carried out by distributing product to several location strategies and 4) advertising strategy, direct invitations to tenders, making flyers and banners, inviting Muslim teachers and opening deposits every week.